Analisis Karakter Rasa Ingin Tahu Peserta Didik tentang Materi Mengutamakan Kejujuran dan Menegakkan Keadilan pada Siswa Kelas VIII SMP Negeri 15 Padang - Septian, Aldi; Rahman, Rini (Lembaga Yasin AlSys, 2023)
The character of curiosity is one of the character values that can be instilled in students as an effort to build national character. The results of interviews with PAI teachers at SMPN 15 Padang show that students' curiosity in class VIII is low with indicators consisting of (1) asking teachers and friends about the subject matter, (2) showing an attitude of interest and disinterest in discussing a material, (3) seek information from various sources about subject matter, (4) Actively discuss in groups to find answers. The aim of this research is to describe the results of an analysis of students' curiosity in classes VIII 3 and VIII 6 of SMPN 15 Padang regarding the material Prioritizing Honesty and Upholding Justice. This research uses quantitative methods with a quantitative descriptive approach. The data collection technique in this research is by distributing questionnaires and documentation. The results of this research show that students' desire to ask teachers and friends about the material Prioritizing Honesty and Upholding Justice is in the medium classification, namely 59%. The attitude of students being interested or not interested in the material Prioritizing Honesty and Upholding Justice is in the medium classification, namely 62%. Students' desire to seek information from various sources regarding the material Prioritizing Honesty and Upholding Justice is in the medium classification, namely 57%. Students' activeness in group discussions to find answers to the lesson material Prioritizing Honesty and Upholding Justice was in the medium classification, namely 62%.